Humanitarianism Goes to War: Tensions between Violence, Human Rights, and Military Humanism in the Post-Cold War (2022)
This article reconstructs and problematizes the debate on the relationship between humanitarianism and the use of force. Thus, it analyzes the historical turns in the evolution of humanitarianism and the establishment of the new political humanitarianism. We then review the converging agendas of new humanitarianism and a liberal interventionist international order, at the core of which is a transformative, maximalist, and utopian discourse on uman rights. This is followed by a collection of critical perspectives on this post-Cold War military humanism, with special focus on critical studies on humanitarianism and post-positivist analyses of international politics. Finally, some arguments are presented in support of those who believe that humanitarianism should regain the highest degree of neutrality and independence possible, distancing itself from military interventionism and from projects of large-scale transformation of the international system. The text provides a critical review of the specialized literature on contemporary humanitarianism, which is essentially interdisciplinary in nature, combining theoretical and methodological foundations from anthropology, law, philosophy, international relations, and reflections from humanitarian workers in the field.